2023
DOI: 10.3390/molecules28135126
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesised TiO2 Nanoparticles-Mediated Terenna asiatica: Evaluation of Their Role in Reducing Oxidative Stress, Inflammation and Human Breast Cancer Proliferation

Abstract: Oxidative stress and chronic inflammation interplay with the pathogenesis of cancer. Breast cancer in women is the burning issue of this century, despite chemotherapy and magnetic therapy. The management of secondary complications triggered by post-chemotherapy poses a great challenge. Thus, identifying target-specific drugs with anticancer potential without secondary complications is a challenging task for the scientific community. It is possible that green technology has been employed in a greater way in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…(2023). [ 9 ] In another study zinc nanoparticles synthesized using endophytic fungal extract exhibited significant and concentration-dependent anti-inflammatory effects compared to the standard (Nehru et al , 2023)[ 10 ]. In addition, investigation highlighted the anti-inflammatory activity of titanium dioxide nanoparticles synthesized from plant extracts (Srinivasan et al , 2019).…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…(2023). [ 9 ] In another study zinc nanoparticles synthesized using endophytic fungal extract exhibited significant and concentration-dependent anti-inflammatory effects compared to the standard (Nehru et al , 2023)[ 10 ]. In addition, investigation highlighted the anti-inflammatory activity of titanium dioxide nanoparticles synthesized from plant extracts (Srinivasan et al , 2019).…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Iqbal et al synthesized TiO 2 nanoparticles using leaf extract of Zanthoxylum armatum and showed potent cytotoxic activity against 4T1 breast tumor cells [22]. Venkatappa et al prepared TiO 2 nanoparticles using Terenna asiatica fruit extract and carried out an anticancerous activity against the MCF-7 breast cancer cell line [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that due to the many phytochemicals (phenolics, terpenoids, etc), plant extract can act as a reducing and stabilizing agent by converting metal salt into nano form [16,17]. There are many studies reported synthesis of metallic nanoparticles using plants extract of jasmine flower [18], papaya [19], Piper nigrum, Coriandrum sativum, Syzygium aromaticum [20], rosemary, ginger [21], Impatiens rothii [22], Terenna asiatica [23], Garcinia mangostana [24], Iranian propolis [25], mango [26].…”
Section: Introductionmentioning
confidence: 99%